Training strongly the speed of the competition and its impact on the size of the heart muscle and the completion of the run 800 meters under 20 years - SABEEH KAREEM, WISAL (International Journal of Psychosocial Rehabilitation, 2020)
Every physical effort of a sports competition has its own adaptations on different body systems, the 800-meter running competition has different functional responses and adjustments than other athletics competition and records from time to time, which indicates that there have been efforts of scientists and trainers to reach the best ways and means and methods to achieve the achievements of the new gym to conduct studies and research scientifically studied and therefore we find that systematic and continuous training and hold the knowledge of physiological adaptations that occur from which lead to the upgrading of sports and access to a higher level, which is the main purpose of the athlete in local and international competitions, adoption researchers experimental approach equal groups and identify the research society youth ran 800 meters The reality of (20) hostility toward the reconstruction of under 20 years and the application of competition and its impact speed strongly exercises the size of the heart muscle and ran 800 meters under 20 years on the Pilot Group for eight weeks, three units per week, training in the use of SPSS statistical bag data processing and the results, including the researchers reaching the most important conclusions that strongly training competition speed has a positive impact on the adaptation of the printed volume of the heart muscle and the achievement of the players, demonstrating the effectiveness of the exercise during the duration of the preparation of the Pilot Group. The researchers recommend the introduction of physiological tests and measurements through the use of the latest equipment and tools in the evaluation of the conduct of the training process.